2011
DOI: 10.1161/circulationaha.110.009928
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Cardiac Troponin T Assay and the Risk of Incident Cardiovascular Disease in Women With and Without Diabetes Mellitus

Abstract: Background Very low levels of cardiac troponin T associate with increased risk of cardiovascular death in patients with stable chronic coronary disease. Whether high-sensitivity cardiac troponin T (hsTnT) levels associate with adverse cardiovascular outcomes in individuals without cardiovascular disease (CVD) has not been well studied. Methods and Results Utilizing two complementary study designs, we evaluated the relationship between baseline cardiac troponin and incident CVD events among diabetic and non-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 29 publications
5
96
0
5
Order By: Relevance
“…Higher proportions have been reported in other cohorts (eg, 39% in the BARI 2D [Bypass Angioplasty Revascularization Investigation 2 Diabetes] trial) 10. In patients with diabetes mellitus with and without established cardiovascular disease, cardiac troponin concentrations are a significant predictor of myocardial infarction, stroke, heart failure, and cardiovascular death 9, 10, 23, 24. As a result, there is considerable interest in identifying treatment strategies that might modify troponin concentrations and thus confer cardiovascular benefit.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Higher proportions have been reported in other cohorts (eg, 39% in the BARI 2D [Bypass Angioplasty Revascularization Investigation 2 Diabetes] trial) 10. In patients with diabetes mellitus with and without established cardiovascular disease, cardiac troponin concentrations are a significant predictor of myocardial infarction, stroke, heart failure, and cardiovascular death 9, 10, 23, 24. As a result, there is considerable interest in identifying treatment strategies that might modify troponin concentrations and thus confer cardiovascular benefit.…”
Section: Discussionmentioning
confidence: 87%
“…Although a reduction in cardiovascular morbidity and mortality has been a major goal of therapy in patients with T2DM, therapeutic strategies focused on intensive glycemic control in these patients have largely failed to show a substantial impact on cardiovascular morbidity and mortality, at least in the short term 5, 6, 7, 8. Circulating concentrations of cardiac troponin, a marker of myocardial injury, and natriuretic peptides (NPs), markers of myocardial stress, have emerged as powerful predictors of cardiovascular risk in stable patients with and without T2DM 9, 10, 11, 12, 13. Both markers have also been associated with abnormalities in glucose metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase in sensitivity due to lower cut-off values came at the expense of a decreased specificity 12 : Elevations of cardiac troponin levels turned out not to be specific for acute myocardial infarction, but were also associated with several other acute and chronic conditions like myocarditis, heart failure, pulmonary embolism, stroke, stable coronary artery disease, type 2 diabetes mellitus, decreased renal function and as the result of prolonged exercise 32,[71][72][73][74][75][76][77][78][79][80] . Since the cut-off values of the current diagnostic algorithms are specifically aimed at not missing subjects with acute myocardial infarction (thus the sensitivity is rather high), this may lead to an overdiagnosis or even an overtreatment of patients with persistently elevated cardiac troponin concentrations 81,82 .…”
Section: The Expense and Opportunities Of High-sensitivity Cardiac Trmentioning
confidence: 99%
“…Several of these studies showed that (slightly, even below the 99the percentile) elevated cardiac troponin concentrations reflect future or (sub)clinical disease, and are associated with an unfavorable prognosis, an increased risk for cardiovascular disease and mortality 77,78,[83][84][85][86][87] . These findings indicate a potential role of cardiac troponins in secondary prevention.…”
Section: The Expense and Opportunities Of High-sensitivity Cardiac Trmentioning
confidence: 99%